Penerapan Aplikasi ATLAS Terhadap Proses Penilaian Risiko (Studi Kasus pada KAP di Sidoarjo) - Annisa Nathania Dewi; Acynthia Ayu Wilasittha (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2024)
This research aims to determine the level of application of the ATLAS application to the risk assessment process at one of the Public Accounting Firms (KAP) in Sidoarjo. The research method used is descriptive qualitative with data collection techniques through observation and interviews with senior and junior auditors at one of the KAP in Sidoarjo. The results of this research are that the ATLAS application can be applied optimally and has an effect on the risk assessment process because this application can help auditors carry out the audit process in a more structured and orderly manner. Implementing the ATLAS application can increase the effectiveness and efficiency of the risk assessment process at KAP, thus making the ATLAS application a useful tool for improving the quality of the risk assessment process at KAP. Apart from that, the ATLAS application can also help auditors provide more rational and objective audit opinions.